Rare Orchids of the North Eastern Region and their Conservation - Varmar, J. C.; Sahni, K. C. (Indian Forester, 1976)
In India 1300 species of orchids are known to occur and the N.E. Region accounts for 600 species. Much less attention has been paid to conservation of floral compared to the publicity given to fatuna like the vanishing rhinoceros and the threstaned tiger. Outstanding, rare and spectacular orchids are highlighted such as Vanda coerulea the blue orchid of Meghalaya which has vanished from the wild. Paphiopedilum fairieanum the ladies slipper orchid popularly called the 'lost orchid' which carried a prize of Â£1000 for its collection from tbe wild Diplomeris hirsuta the spectacular orchid of Darjeeling and Sikkim which inhabits big boulders and is threatened due to intense road building activity, Galeola falconeri the tallest orchid of the eastern region attaining 3 m in height and standhing out majestically in the forests of Kameng, Cymbidium grandiflorum, G. giganteum etc. and a host of handsome Dendrobiums some of which produce a mass effect of blooms. Cultural techniques and information on potting and compost is given. It is emphasized that there is an urgent need to have a botanical survey of Arunachal, Sikkim, Manipur, Nagaland etc., wtih an attempt to save spectacular flora like orchids, plants of great botanical interest or ancient flora of antiquity either in botanic reserves, sanctuaries or preservation plots. A chain of sanctuaries are desired to preserve the entire ecosystem. Rearing of threatened flora in botanic garden is suggested.